X-shooting ULLYSES: massive stars at low metallicity : V. Effect of metallicity on surface abundances of O stars - Martins, Fabrice; Bouret, J.-C.; Hillier, D. J.; Brands, S. A.; Crowther, P. A.; Herrero, A.; Najarro, F.; Pauli, D.; Puls, J.; Ramachandran, Varsha; Sander, Andreas A. C.; Vink, J. S. (Astronomy and astrophysics, 2024)
Context. Massive stars rotate faster, on average, than lower mass stars. Stellar rotation triggers hydrodynamical instabilities which transport angular momentum and chemical species from the core to the surface. Models of high-mass stars that include these processes predict that chemical mixing is stronger at lower metallicity. Aims. We aim to test this prediction by comparing the surface abundances of massive stars at different metallicities. Methods. We performed a spectroscopic analysis of single O stars in the Magellanic Clouds (MCs) based on the ULLYSES and XShootU surveys. We determined the fundamental parameters and helium, carbon, nitrogen, and oxygen surface abundances of 17 LMC and 17 SMC non-supergiant O6-9.5 stars. We complemented these determinations by literature results for additional MCs and also Galactic stars to increase the sample size and metallicity coverage. We investigated the differences in the surface chemical enrichment at different metallicities and compared them with predictions of three sets of evolutionary models. Results. Surface abundances are consistent with CNO-cycle nucleosynthesis. The maximum surface nitrogen enrichment is stronger in MC stars than in Galactic stars. Nitrogen enrichment is also observed in stars with higher surface gravities in the SMC than in the Galaxy. This trend is predicted by models that incorporate chemical transport caused by stellar rotation. The distributions of projected rotational velocities in our samples are likely biased towards slow rotators. Conclusions. A metallicity dependence of surface abundances is demonstrated. The analysis of larger samples with an unbiased distribution of projected rotational velocities is required to better constrain the treatment of chemical mixing and angular momentum transport in massive single and binary stars.
Online veröffentlicht: 30 August 2024
Gesehen am 12.03.2025